Penanganan Pengungsi Internasional dalam Kerangka Implementasi Tujuan Pembangunan Berkelanjutan (TPB) di Indonesia - Alifa Salsabila; Prasetyo Hadi Purwandoko (Faculty of Law Universitas Sebelas Maret, 2019)
This paper describes and examines the handling of international refugees within the framework of implementing Sustainable Development Goals (TPB) in Indonesia. The research in this paper is a normative research using a conceptual approach to the principles of international law and human rights law, as well as the statute approach to the Republic of Indonesia Presidential Regulation No. 125 of 2016 concerning Refugee Handling from Abroad and Presidential Regulation No. 59 of 2017 concerning Implementation Achievement of Sustainable Development Goals (TPB). Indonesia as a transit country does not ratify the 1951 Convention on the Status of Refugees and the 1967 Protocol on Refugee Status. The results of the study show that even though it has not been done optimally, humanitarian response to Indonesian foreign policy towards international refugees is a form of Indonesia’s attachment to the moral of human rights and the principles of international law. Thus, this humanitarian response is a justification for the handling of international refugees within the framework of implementing Sustainable Development Goals (TPB) in Indonesia.Keywords: